Feminist Perspective in the Selected Novels of Anita Nair: Ladies Coupé and Mistress - P. Bala Muthu Marieswari (Language in India, 2014)
ract Post-colonial feminist literature has always carried the heavy burden of dealing with layers of misinterpretation of traditions and religions. At the center of this dilemma is the role of woman and her dependence, economically and socially. The more traditional a postcolonial society is, the more problematic the question of women’s emancipation is. Therefore, the more passionate its women novelists like Anita Nair raise what many readers might consider taboo questions about the role of woman in contemporary post-colonial India. Among the novels of Anita Nair, Ladies coupé and Mistress are chosen for this paper. Through these novels Anita Nair has signalled the arrival of a sensitive writer who could perceive deeper mysteries in people’s personalities and take the reader on a wonderful journey of discovery. These novels have a talent for probing the insular world. In these pages I shall attempt an appreciation of Anita Nair’s powers for the delineation of the deeper layers of the woman’s personality